De la ley de justicia y paz a la ley de víctimas y restitución de tierras. de la indignación a la reconciliación (2012)
The approaches of transitional justice aim to restore the natural conditions of State institutions, the way of truth, justice and reparation. At recent times, the Colombian legal system incorporated two special and complementary models of this approach of justice (i.e. the Law of Victims and Restitution of Lands and the Law of Justice and Peace). Starting from a succinct analysis of two aforementioned models of transitional justice, I suggest that the occurrence of the armed conflict and the existence of victims demonstrate the practical weakness of the political State and the fragility of the democratic core. It is defined by defending the thesis that the aforementioned models of transitional justice solve the problem partially (material areas of repair), but that they themselves must be accompanied by the civil society through the creation of a degree of awareness of the conflict (symbolic spaces of repair) inspired by the moral sense of outrage, as being the only means of reconciliation.